1993
DOI: 10.1111/j.1834-7819.1993.tb05495.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodical gingival bleeding as a presenting symptom of periodontitis due to underlying cyclic neutropenia. Case report

Abstract: A 13-year-old boy presenting with spontaneous and periodical gingival bleeding accompanied by fever was thoroughly examined in order to determine the underlying aetiology of the gingival bleeding. Following repeated blood tests, the patient was diagnosed as having cyclic neutropenia. Thus, it was suggested, gingival bleeding, especially when spontaneous and periodical, should be carefully investigated to eliminate the possibility of cyclic neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Tozum et al 26 reported that regular follow-up visits resulting in improved plaque control may improve the systemic condition in patients with SCN. Since several reports [26][27][28] indicate that regular follow-up visits and adequate plaque control result in clinical improvement of periodontal disease in systemically compromised patients, we arranged regular dental appointments for our two patients following initial periodontal therapy. Neutrophils in gingival connective tissue, junctional epithelium, and the gingival sulcus, which provide a barrier between dental plaque and the periodontium, are vital for protecting an individual from infections.…”
Section: Results Of Peripheral Blood Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tozum et al 26 reported that regular follow-up visits resulting in improved plaque control may improve the systemic condition in patients with SCN. Since several reports [26][27][28] indicate that regular follow-up visits and adequate plaque control result in clinical improvement of periodontal disease in systemically compromised patients, we arranged regular dental appointments for our two patients following initial periodontal therapy. Neutrophils in gingival connective tissue, junctional epithelium, and the gingival sulcus, which provide a barrier between dental plaque and the periodontium, are vital for protecting an individual from infections.…”
Section: Results Of Peripheral Blood Testsmentioning
confidence: 99%
“…Since reduction in neutrophil count and/or function results in an inability of the host to defend against infections, such individuals express a variety of conditions that may include lymph node enlargement, multiple abscess formation, respiratory tract infections, and aggressive periodontal destruction characterized by severe gingival inflammation, edema, periodontal pocket formation, and tooth mobility. 27,29,30 Defraia and Marinelli 31 also reported a severe periodontal and periodontal treatment for neutropenic patients should be prevention of periapical and periodontal infection without surgical intervention, especially in children.…”
Section: Treatmentmentioning
confidence: 94%
“…A general malaise, fever, lymphadenopathy, and oral ulcerations are very common findings during neutropenic periods [8]. Severe periodontitis and oral ulcerations have been reported in the majority of the recorded cases, meanwhile ulcerations may be the unique oral manifestation in about 20% of patients [9–11]. The mucosal lesions can affect any part of the oral mucosa during the neutropenic phases and cause pain and very intense burning that could discourage the patient to maintain a good oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Prädilektionsstellen sind die Mundhöhle sowie die Anogenitalregion [2,8,10,12,13]. Prädilektionsstellen sind die Mundhöhle sowie die Anogenitalregion [2,8,10,12,13].…”
Section: Therapie Und Verlaufunclassified